Glass composition for glass fiber, glass fiber and glass fiber reinforced resin molded product
By melting and recycling glass fibers into glass fibers and optimizing the composition of glass compositions for glass fibers, the problems of deterioration in the operational properties and uneven fiber diameters in the manufacturing process are solved, and high-quality glass fibers are achieved Reinforced resin molded products.
Patent Information
- Application Number
- CN202280042154.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-29
- Filing Date
- 2022-06-10
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-06-10
Abstract
Description
Technical Field
[0001] The present invention relates to a glass composition for glass fiber, glass fiber and a glass fiber reinforced resin molded product. Background Art
[0002] Conventionally, glass fiber reinforced resin molded products using E glass fiber (glass fiber having an E glass composition) have been widely used as metal substitute materials for automobile parts and the like because they contribute to reducing environmental burdens by improving fuel efficiency along with weight reduction.
[0003] In recent years, with the increasing concern for recycling, in order to further reduce the environmental burden, people are studying the technology of extracting E glass fibers from glass fiber reinforced resin molded products and recycling them. As a method for extracting glass fibers from glass fiber reinforced resin molded products, for example, the following recovery method is known: glass fiber reinforced plastic waste is dry-distilled at a thermal decomposition temperature of 320 to 600° C. in a thermal decomposition chamber, and after the thermal decomposition, the decomposition gas is brought into contact with water to recover the liquid component of the decomposition product, and the glass fiber is recovered at the same time (for example, refer to Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 6-234879 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, when glass fiber reinforced resin molded products are manufactured by injection molding using E glass fibers (hereinafter sometimes referred to as recycled glass fibers) recovered from glass fiber reinforced plastic waste and other glass fiber reinforced resin molded products, there is a problem of deterioration in workability. Specifically, the deterioration in workability refers to the situation that when the recycled glass fibers and resin are kneaded to produce resin pellets for injection molding, the recycled glass fibers clog the kneading machine, thereby failing to produce resin pellets.
[0009] The present inventors have studied the above problems and found that the above deterioration in workability can be solved by melting glass raw materials containing recycled glass fibers to produce molten glass and spinning the molten glass to produce glass fibers.
[0010] However, glass fibers obtained by using a glass raw material including recycled glass fibers in the above manner have the disadvantage that fiber diameters vary.
[0011] The present inventors have conducted in-depth studies on the above-mentioned undesirable situation and found that substances (especially inorganic substances) derived from additives other than E glass fibers contained in glass fiber-reinforced resin molded products remain on the surface of recycled glass fibers. When a glass composition containing recycled glass fibers is used as a glass raw material to manufacture glass fibers, the substances derived from the additives cause the composition of the glass fibers to change, resulting in uneven fiber diameters of the glass fibers.
[0012] The present inventors have conducted further studies based on the above findings and have found that substances similar to those derived from the above additives may be contained as impurities in a glass fiber mineral material constituting a glass raw material. When a glass raw material is prepared using a glass fiber mineral material containing the substances similar to those derived from the above additives as impurities, the fiber diameters of glass fibers produced using the glass raw material also become uneven.
[0013] Therefore, an object of the present invention is to provide a glass composition for glass fibers which can suppress the unevenness of the fiber diameter of glass fibers even when the glass fibers are affected by the same substances as those derived from the above-mentioned additives.
[0014] Means for solving problems
[0015] In order to achieve the above-mentioned object, the glass composition for glass fiber of the present invention is characterized in that it contains SiO2 in the range of 45.60 to 59.00 mass %, Al2O3 in the range of 10.00 to 16.00 mass %, CaO in the range of 17.00 to 25.00 mass %, TiO2 in the range of 0.01 to 9.50 mass %, P2O5 in the range of 0.03 to 7.00 mass %, Zn in the range of 0.00 to 9.50 mass % relative to the total amount of the glass composition for glass fiber. O, SO3 in the range of 0.00 to 2.00 mass%, ZnO and SO3 in the range of 0.01 to 11.50 mass%, Na2O, K2O and Li2O in the range of 0.00 to 2.00 mass%, the content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO, and the content SO of SO3 satisfy the following formula (1),
[0016] 15.0≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤690.1…(1).
[0017] According to the glass composition for glass fiber of the present invention, by making the content of SiO2, the content of Al2O3, the content of CaO, the content of TiO2, the content of P2O5, the content of ZnO and the content of SO3 relative to the total amount of the glass composition for glass fiber within the above ranges, and by making the content of SiO2 S1, the content of Al2O3 A, the content of CaO C, the content of TiO2 T, the content of P2O5 P, the content of ZnO and the content of SO of SO satisfy the formula (1), even if the glass fiber formed by the glass composition for glass fiber of the present invention is affected by the same substance as the substance derived from the additive, the unevenness of the fiber diameter can be suppressed when the glass fiber has a circular cross section. The above-mentioned additive is a substance remaining on the surface of the glass fiber recovered from the glass fiber reinforced resin molded product containing E glass fiber.
[0018] In addition, the glass composition for glass fibers of the present invention can make the strength, thermal expansion coefficient, elastic modulus and refractive index of glass fibers formed from the glass composition for glass fibers equal to those of conventional E glass fibers. The thermal expansion coefficient and elastic modulus can be measured by the method described below.
[0019] Here, the general E glass fiber refers to a glass fiber having an E glass composition. The E glass composition is a composition containing SiO2 in a range of 52.0 to 56.0 mass %, Al2O3 in a range of 12.0 to 16.0 mass %, MgO and CaO in a range of 20.0 to 25.0 mass % in total, and B2O3 in a range of 5.0 to 10.0 mass % relative to the total amount of the glass fiber.
[0020] In the glass composition for glass fiber of the present invention, the content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO and the content SO of SO preferably satisfy the following formula (2), more preferably satisfy the following formula (3), and further preferably satisfy the following formula (4).
[0021] 33.5≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤666.7…(2)
[0022] 47.8≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤579.8…(3)
[0023] 91.5≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤552.0…(4)
[0024] In the glass composition for glass fiber of the present invention, by making the content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO and the content SO of SO3 satisfy the above formula (2), when the glass fiber has a circular cross section, the unevenness of the fiber diameter can be further suppressed. In addition, in the glass composition for glass fiber of the present invention, by making the above SI, A, C, T, P, Z and SO satisfy the above formula (3), when the glass fiber has a circular cross section, the unevenness of the fiber diameter can be further suppressed, and when the glass fiber has a flat cross section, the unevenness of the ratio of the major axis to the minor axis (major axis / minor axis, hereinafter sometimes referred to as the profile ratio) can be suppressed. Furthermore, in the glass composition for glass fiber of the present invention, by making the above SI, A, C, T, P, Z and SO satisfy the above formula (4), when the glass fiber has a circular cross section, the unevenness of the fiber diameter can be further suppressed, and when the glass fiber has a flat cross section, the unevenness of the profile ratio can be suppressed. In addition, the thermal expansion coefficient of the glass fiber can be made within ±3% of the thermal expansion coefficient of the general E glass fiber. It should be noted that the thermal expansion coefficient of the general E glass fiber is 5.6 ppm / °C.
[0025] Furthermore, the glass fiber of the present invention is characterized by being formed from any one of the above-mentioned glass compositions for glass fibers.
[0026] Furthermore, the glass fiber reinforced resin molded article of the present invention is characterized by containing the glass fiber of the present invention. DETAILED DESCRIPTION
[0027] Next, embodiments of the present invention will be described in further detail.
[0028] The glass composition for glass fiber of the present embodiment contains SiO2 in a range of 45.60 to 59.00 mass %, Al2O3 in a range of 10.00 to 16.00 mass %, CaO in a range of 17.00 to 25.00 mass %, TiO2 in a range of 0.01 to 9.50 mass %, P2O5 in a range of 0.03 to 7.00 mass %, ZnO in a range of 0.00 to 9.50 mass %, and ZnO in a range of 0.00 to 1.00 mass %. 2.00 mass% of SO3, 0.01-11.50 mass% of ZnO and SO3 in total, and 0.00-2.0 mass% of Na2O, K2O and Li2O in total, the SiO2 content SI, the Al2O3 content A, the CaO content C, the TiO2 content T, the P2O5 content P, the ZnO content Z and the SO3 content SO satisfy the following formula (1).
[0029] 15.0≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤690.1…(1)
[0030] In the glass composition for glass fiber of the present embodiment, when SiO2 relative to the total amount of the glass composition for glass fiber is less than 45.60% by mass, the mechanical strength of the glass fiber obtained by using the glass composition for glass fiber is greatly reduced, and the function of the glass fiber as a reinforcing material in the glass fiber reinforced resin molded product is impaired. In addition, the glass fiber is easily deteriorated when placed in an acidic environment. On the other hand, when SiO2 relative to the total amount of the glass composition for glass fiber exceeds 59.00% by mass, the viscosity at high temperature becomes high, thus causing the temperature of the molten glass raw material to become high, and from the viewpoint of manufacturing cost, it is not suitable for the industrial manufacture of glass fiber.
[0031] In the glass composition for glass fiber of the present embodiment, the content of SiO2 relative to the total amount of the glass composition for glass fiber is preferably in the range of 47.60 to 57.90 mass %, more preferably in the range of 48.60 to 56.90 mass %, further preferably in the range of 49.60 to 56.40 mass %, particularly preferably in the range of 50.60 to 55.90 mass %, and most preferably in the range of 51.60 to 55.40 mass %.
[0032] In the glass composition for glass fiber of the present embodiment, when the content of Al2O3 relative to the total amount of the glass composition for glass fiber is less than 10.00 mass %, devitrification is likely to occur. On the other hand, when the content of Al2O3 relative to the total amount of the glass composition for glass fiber exceeds 16.00 mass %, the viscosity at high temperature becomes high, thereby causing the temperature of the molten glass raw material to become high, which is not suitable for industrial production of glass fiber from the viewpoint of production cost.
[0033] In the glass composition for glass fiber of the present embodiment, the content of Al2O3 relative to the total amount of the glass composition for glass fiber is preferably in the range of 10.60 to 15.40 mass %, more preferably in the range of 10.10 to 15.10 mass %, further preferably in the range of 11.10 to 14.90 mass %, particularly preferably in the range of 11.90 to 14.70 mass %, and most preferably in the range of 12.40 to 14.40 mass %.
[0034] In the glass composition for glass fiber of the present embodiment, when the content of CaO relative to the total amount of the glass composition for glass fiber is less than 17.0% by mass, the viscosity of the glass at high temperature becomes high, so the meltability is deteriorated. On the other hand, when the content of CaO relative to the total amount of the glass composition for glass fiber exceeds 25.00% by mass, devitrified materials are easily generated in the sleeve, which may cause breakage during spinning or may cause the formation of glass fibers containing devitrified materials.
[0035] In the glass composition for glass fiber of the present embodiment, the content of CaO relative to the total amount of the glass composition for glass fiber is preferably in the range of 18.10 to 24.40 mass %, more preferably in the range of 19.10 to 23.90 mass %, further preferably in the range of 19.60 to 23.40 mass %, particularly preferably in the range of 20.10 to 23.10 mass %, and most preferably in the range of 20.60 to 22.90 mass %.
[0036] In the glass composition for glass fiber of the present embodiment, when the content of TiO2 relative to the total amount of the glass composition for glass fiber is less than 0.01% by mass, the viscosity at high temperature becomes high, thus causing the temperature of the molten glass raw material to become high, and from the viewpoint of manufacturing cost, it is not suitable for industrial manufacturing of glass fiber. On the other hand, when the content of TiO2 relative to the total amount of the glass composition for glass fiber exceeds 9.50% by mass, the elastic modulus of the glass composition for glass fiber increases, significantly deviating from the elastic modulus of standard E glass. In addition, the liquidus temperature of the glass composition for glass fiber increases significantly, so it is impossible to manufacture stable glass fiber. In addition, the glass is colored, and the refractive index greatly deviates from the standard E glass.
[0037] In the glass composition for glass fiber of the present embodiment, the content of TiO2 relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.10 to 4.90 mass%, more preferably in the range of 0.20 to 3.90 mass%, further preferably in the range of 0.30 to 2.40 mass%, particularly preferably in the range of 0.50 to 1.40 mass%, and most preferably in the range of 0.60 to 1.10 mass%.
[0038] In the glass composition for glass fibers of the present embodiment, when the content of P2O5 relative to the total amount of the glass composition for glass fibers exceeds 7.00 mass %, the liquidus temperature of the glass composition for glass fibers increases significantly, and thus stable glass fibers cannot be produced.
[0039] In the glass composition for glass fiber of the present embodiment, the content of P2O5 relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.20 to 4.90 mass %, more preferably in the range of 0.30 to 2.90 mass %, further preferably in the range of 0.40 to 1.90 mass %, particularly preferably in the range of 0.50 to 1.40 mass %, and most preferably in the range of 0.70 to 1.20 mass %.
[0040] In the glass composition for glass fiber of the present embodiment, if the content of ZnO relative to the total amount of the glass composition for glass fiber exceeds 9.50 mass %, the liquidus temperature of the glass composition for glass fiber increases significantly, and stable glass fiber cannot be manufactured. In addition, the elastic modulus and refractive index deviate greatly from those of ordinary E glass.
[0041] In the glass composition for glass fiber of the present embodiment, the content of ZnO relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.20 to 4.90 mass %, more preferably in the range of 0.30 to 2.90 mass %, further preferably in the range of 0.40 to 1.90 mass %, particularly preferably in the range of 0.50 to 1.40 mass %, and most preferably in the range of 0.70 to 1.20 mass %.
[0042] In the glass composition for glass fiber of the present embodiment, when the content of SO3 relative to the total amount of the glass composition for glass fiber exceeds 2.0 mass %, reboiling bubbles are easily generated, which becomes the cause of broken fibers or hollow fibers in the manufacture of glass fiber. Here, reboiling bubbles refer to bubbles that reboil due to the decrease in the solubility of the gas dissolved in the molten glass due to the increase in the temperature of the molten glass. In addition, hollow fibers refer to glass fibers that are obtained by spinning molten glass containing bubbles and have cavities caused by bubbles inside. The presence of cavities inside the glass fiber becomes the cause of the reduction in the strength of the glass fiber.
[0043] In the glass composition for glass fibers of the present embodiment, the content of SO 3 relative to the total amount of the glass composition for glass fibers is preferably in the range of 0.01 to 1.40 mass %, more preferably in the range of 0.05 to 0.90 mass %, and further preferably in the range of 0.10 to 0.40 mass %.
[0044] In the glass composition for glass fiber of the present embodiment, if the total content of ZnO and SO3 relative to the total amount of the glass composition for glass fiber is less than 0.01% by mass, the clarity of the glass becomes insufficient, bubbles are easily contained in the glass fiber, and the possibility of glass fiber breakage caused by the bubbles becomes high, resulting in deterioration in productivity. On the other hand, if the total content of ZnO and SO3 relative to the total amount of the glass composition for glass fiber exceeds 11.50% by mass, it is easy to produce spinning of glass fiber in a state where unmelted components remain, and the unmelted components become a major cause of glass fiber breakage, resulting in deterioration in productivity.
[0045] In the glass composition for glass fiber of the present embodiment, the total content of ZnO and SO3 relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.10 to 3.90 mass %, more preferably in the range of 0.40 to 2.40 mass %, further preferably in the range of 0.60 to 2.20 mass %, particularly preferably in the range of 0.80 to 1.90 mass %, and most preferably in the range of 1.10 to 1.60 mass %.
[0046] In the glass composition for glass fiber of the present embodiment, P2O5, ZnO, SO3, and TiO2 are derived from impurities contained in the glass fiber mineral material used as glass raw material and clarifiers added to the glass raw material when the glass is melted. In addition, when a part of the glass raw material includes glass fiber recovered from a glass fiber reinforced resin molded product containing E glass fiber, P2O5, ZnO, SO3, and TiO2 may be derived from additives remaining on the surface of the glass fiber contained in the above-mentioned glass fiber reinforced resin molded product. Here, as the resin used in the above-mentioned glass fiber reinforced resin molded product, the resin forming the glass fiber reinforced resin molded product of the present embodiment described later, in particular, a thermoplastic resin, can be cited. In addition, examples of the above-mentioned additives include flame retardants (e.g., phosphorus-based flame retardants, inorganic flame retardants), colorants (e.g., titanium oxide, zinc oxide, zinc sulfide, carbon black), antioxidants (e.g., sulfur-based antioxidants, phosphorus-based antioxidants), plasticizers (e.g., phosphoric acid-based plasticizers), fillers (e.g., talc, calcium carbonate, aluminum hydroxide), ultraviolet absorbers, antistatic agents, modifiers, and the like.
[0047] In the glass composition for glass fiber of the present embodiment, if the total content of Na2O, K2O and Li2O relative to the total amount of the glass composition for glass fiber exceeds 2.0 mass %, the strength of the glass fiber formed from the glass composition for glass fiber decreases, and the deviation from the strength of the ordinary E glass fiber increases.
[0048] In the glass composition for glass fiber of the present embodiment, the total content of Na2O, K2O and Li2O relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.11 to 0.40 mass%, more preferably in the range of 0.21 to 1.20 mass%, further preferably in the range of 0.31 to 0.90 mass%, particularly preferably in the range of 0.41 to 0.79 mass%, and most preferably in the range of 0.51 to 0.59 mass%.
[0049] Furthermore, the glass composition for glass fiber of the present embodiment may contain 0.00 to 8.00 mass % of B2O3, 0.00 to 3.00 mass % of MgO, 0.00 to 2.00 mass % of Fe2O3, and 0.00 to 2.00 mass % of F2 relative to the total amount of the glass composition for glass fiber.
[0050] In the glass composition for glass fiber of the present embodiment, the content of B2O3 relative to the total amount of the glass composition for glass fiber is preferably in the range of 2.60 to 7.40 mass %, more preferably in the range of 3.10 to 6.90 mass %, further preferably in the range of 3.60 to 6.70 mass %, particularly preferably in the range of 4.10 to 6.70 mass %, especially preferably in the range of 4.60 to 6.40 mass %, extremely preferably in the range of 5.10 to 6.40 mass %, and most preferably in the range of 5.60 to 6.40 mass %.
[0051] In the glass composition for glass fiber of the present embodiment, the content of MgO relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.30 to 2.40 mass %, more preferably in the range of 0.60 to 1.90 mass %, further preferably in the range of 0.70 to 1.40 mass %, particularly preferably in the range of 0.80 to 1.20 mass %, and most preferably in the range of 0.90 to 1.00 mass %.
[0052] In the glass composition for glass fibers of the present embodiment, the content of Fe 2 O 3 relative to the total amount of the glass composition for glass fibers is preferably in the range of 0.10 to 0.90 mass %, more preferably in the range of 0.10 to 0.40 mass %.
[0053] In the glass composition for glass fibers of the present embodiment, the content of F2 relative to the total amount of the glass composition for glass fibers is preferably in the range of 0.10 to 1.90 mass %, and more preferably in the range of 0.10 to 0.90 mass %.
[0054] Furthermore, the glass composition for glass fibers according to the present embodiment may contain ZrO 2 , Cr 2 O 3 , and SnO 2 .
[0055] In the glass composition for glass fiber of the present embodiment, the content of ZrO2 relative to the total amount of the glass composition for glass fiber is preferably less than 0.50 mass%, more preferably less than 0.40 mass%, further preferably less than 0.20 mass%, particularly preferably less than 0.10 mass%, and most preferably less than 0.05 mass%.
[0056] In the glass composition for glass fiber of the present embodiment, the content of Cr2O3 relative to the total amount of the glass composition for glass fiber is preferably less than 0.10 mass %, more preferably less than 0.05 mass %. As long as the content of Cr2O3 in the glass fiber formed from the glass composition for glass fiber of the present embodiment is within the above range, when a molded product such as a composite material is made, the occurrence of color unevenness, color tone change, poor appearance, etc. caused by the coloring of the glass can be suppressed.
[0057] In the glass composition for glass fiber of the present embodiment, the content of SnO2 relative to the total amount of the glass composition for glass fiber is preferably less than 1.00 mass%, more preferably less than 0.50 mass%, further preferably less than 0.40 mass%, particularly preferably less than 0.20 mass%, especially preferably less than 0.10 mass%, and most preferably less than 0.05 mass%.
[0058] In addition, the glass composition for glass fiber of the present embodiment may contain oxides of Ba, Sr, Co, Ni, Cu, Mo, W, Ce, Y, La, Bi, Gd, Pr, Sc or Yb as impurities derived from raw materials, and the total content of the oxides relative to the total amount of the glass composition for glass fiber is less than 1.00 mass%. In particular, when the glass composition for glass fiber of the present embodiment contains BaO, SrO, CoO, NiO, CuO, MoO3, WO3, CeO2, Y2O3, La2O3, Bi2O3, Gd2O3, Pr2O3, Sc2O3 or Yb2O3 as impurities, the content of each impurity alone is preferably less than 0.50 mass%, more preferably less than 0.40 mass%, further preferably less than 0.20 mass%, particularly preferably less than 0.10 mass%, particularly preferably less than 0.05 mass%, and most preferably less than 0.01 mass%.
[0059] The glass composition for glass fiber of the present embodiment is a composition as follows: a glass composition obtained by mixing, melting, etc., a glass raw material containing a glass fiber mineral material composed of a plurality of ores or materials refined from ores (sometimes also referred to as a refined material derived from an ore) and homogenizing it. The above-mentioned glass raw material may contain glass fibers (recycled glass fibers) recovered from glass fiber reinforced resin molded products containing E glass fibers. Here, from the viewpoint of reducing the environmental burden, the glass composition for glass fiber of the present embodiment is preferably a glass composition obtained by homogenizing a glass raw material containing glass fibers recovered from glass fiber reinforced resin molded products containing E glass fibers. The glass fiber mineral raw material determines the type of ore or refined materials derived from ore, and the content ratio of each ore or refined materials derived from ore based on the components contained in the glass fiber mineral raw material and the content rate of each component and the volatilization amount of each component during the melting process, so as to achieve the desired composition. In addition, when the glass raw material contains the glass fiber mineral raw material and the recycled glass fiber, the glass fiber mineral raw material and the recycled glass fiber are determined based on the components contained in the glass fiber mineral raw material and the content rate of each component, the components contained in the recycled glass fiber and the content rate of each component, and the volatilization amount of each component during the melting process, the type of ore or refined materials derived from the ore, the content ratio of each ore or refined materials derived from the ore, and the content ratio of the glass fiber mineral raw material and the recycled glass fiber so as to have a desired composition.
[0060] Examples of the ore include silica sand, feldspar, clay, limestone, etc. Examples of the refined material derived from the ore include silica powder, dolomite, talc, clay, alumina, soda ash, etc.
[0061] In the glass composition for glass fiber of the present embodiment, the content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO and the content SO of SO3 satisfy the following formula (1), and preferably satisfy the following formula (2), more preferably satisfy the following formula (3), and particularly preferably satisfy the following formula (4). In addition, from the viewpoint that the physical properties of the glass fiber formed by the glass composition for glass fiber of the present embodiment are closer to the physical properties of the ordinary E glass fiber, the above SI, A, C, T, P, Z and SO particularly preferably satisfy the following formula (5), extremely preferably satisfy the following formula (6), and most preferably satisfy the following formula (7).
[0062] 15.0≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤690.1…(1)
[0063] 33.5≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤666.7…(2)
[0064] 47.8≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤579.8…(3)
[0065] 91.5≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤552.0…(4)
[0066] 152.6≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤429.8…(5)
[0067] 194.6≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤429.8…(6)
[0068] 245.2≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤353.3…(7)
[0069] In the glass composition for glass fiber of the present embodiment, regarding the content of each component mentioned above, Li as a light element can be measured using an ICP emission spectrometer, and other elements can be measured using a wavelength dispersive fluorescence X-ray analyzer. The determination method is as follows: First, the glass composition for glass fiber is placed in a platinum crucible, and after being kept at a temperature of 1450°C in an electric furnace for 6 hours, it is melted while being stirred to obtain a homogeneous molten glass. Next, the molten glass obtained from the platinum crucible is poured onto a carbon plate, and after being made into cullet, the cullet is crushed and powdered to obtain glass powder. After the glass powder is heated and decomposed with acid, Li as a light element is quantitatively analyzed using an ICP emission spectrometer. After the glass powder is formed into a disc shape using a press, other elements are quantitatively analyzed using a wavelength dispersive fluorescence X-ray analyzer. These quantitative analysis results are converted into oxides to calculate the content and total amount of each component, and the content (mass %) of each component mentioned above is calculated based on these numerical values.
[0070] The glass fiber of the present embodiment is preferably a glass fiber: a glass long fiber composed of any of the above-mentioned glass compositions for glass fibers and having a length of at least 1000 m during manufacture. The glass fiber of the present embodiment can be manufactured by melting and homogenizing the glass raw materials prepared in the manner of the composition of the glass composition for glass fibers of the present embodiment to form molten glass, and spinning the molten glass to form glass fibers. Here, from the viewpoint of reducing the environmental burden, the glass fiber of the present embodiment is preferably manufactured by melting and homogenizing the glass raw materials of the glass fibers recovered from the glass fiber reinforced resin molded product containing E glass fibers to form molten glass, and spinning the molten glass.
[0071] When manufacturing the glass fiber of the present embodiment, first, the glass raw material prepared in the above manner is supplied to a glass melting furnace and melted in a temperature range of 1000 poise or more, specifically, in a temperature range of 1200° C. to 1500° C. to form molten glass. Then, the molten glass melted to the above temperature is ejected from 1 to 8000 nozzle heads or holes controlled to a predetermined temperature, and is drawn by high-speed winding while being cooled and solidified to form glass fibers.
[0072] Here, the glass single fiber (glass filament) ejected from a nozzle head or hole and cooled and solidified usually has a circular cross-sectional shape. On the other hand, when the nozzle head has a non-circular shape and has a protrusion or a cutout for quenching the molten glass, a glass filament with a flat cross-sectional shape can be obtained by controlling the temperature conditions. When the glass filament has a flat cross-sectional shape, as the flat cross-sectional shape, for example, an oblong, an elliptical, and a rectangular shape can be cited. Here, an oblong refers to a shape after the short side of the rectangle is replaced with a semicircle having a diameter equal to the short side.
[0073] When the cross-sectional shape of the glass filament is a perfect circle or a substantially perfect circle, the fiber diameter of the glass filament can be measured in the following manner: for example, first, the glass filament is embedded in a resin such as an epoxy resin, the resin is cured, the cured resin is cut, and the cross section is ground. Next, the cross section of the cured resin is observed using an electron microscope, and the diameter of more than 100 glass filaments exposed in the cross section is measured. Alternatively, the fiber diameter can be measured by performing image processing on an image obtained from an electron microscope using an automatic analysis device.
[0074] On the other hand, when the glass filaments of the present embodiment are included in the glass fiber reinforced resin molded product, the fiber diameter of the above-mentioned glass filaments can be measured in the following manner. For example, first, the cross section of the glass fiber reinforced resin molded product is ground. Then, the filament diameter of the above-mentioned glass filaments is measured in the same manner as the method for measuring the filament diameter of the above-mentioned glass filaments.
[0075] In addition, when the cross-sectional shape of the glass filament is a flat shape, the fiber diameter of the above-mentioned glass filament can be measured in the following manner. For example, first, the cross-sectional area of more than 100 glass filaments is calculated on the basis of the cross-section of the glass filaments that can be observed by using the same method as the method for measuring the filament diameter of the above-mentioned glass filaments. Then, the converted fiber diameter is calculated based on the calculated cross-sectional area. Then, the fiber diameter of the above-mentioned glass filament is calculated by obtaining the average value of the measured or calculated diameter or the converted fiber diameter.
[0076] Here, the converted fiber diameter of the glass filament refers to the diameter of a perfect circle having the same area as the area of the cross-sectional shape of the glass filament. In addition, the cross section of the glass filament refers to a cross section perpendicular to the fiber length direction of the glass fiber.
[0077] The fiber diameter or converted fiber diameter of the glass filament constituting the glass fiber of the present embodiment is, for example, in the range of 3.0 to 100.0 μm, preferably in the range of 4.0 to 70.0 μm, and more preferably in the range of 5.0 to 50.0 μm.
[0078] When the glass filaments constituting the glass fiber of the present embodiment have a flat cross-sectional shape, the ratio of the major axis to the minor axis in the cross section (major axis / minor axis) is, for example, in the range of 2.0 to 10.0, and preferably in the range of 3.0 to 8.0.
[0079] When the glass filaments have a flat cross-sectional shape, the short diameter and long diameter of the glass fiber can be calculated in the following manner. For example, first, the same method as the method for measuring the filament diameter of the glass filaments is used, and on the basis of being able to observe the cross section of the glass filaments, an electron microscope is used to measure the lengths of the long diameter and short diameter of more than 100 glass filaments, wherein the longest side passing through the approximate center of the cross section of the glass filament is taken as the long diameter, and the side orthogonal to the long diameter at the approximate center of the cross section of the glass filament is taken as the short diameter. Then, the short diameter and long diameter of the glass fiber are calculated by finding the average value of the measured values of the long diameter or short diameter.
[0080] The glass fiber reinforced resin molded product of the present embodiment includes the glass fiber of the present embodiment.
[0081] The glass fibers contained in the glass fiber reinforced resin molded product of the present embodiment may be glass fibers processed into various forms. Examples of the forms in which the glass fibers are processed include chopped strands, rovings, and cut fibers.
[0082] The above-mentioned chopped strands refer to glass fibers (also referred to as glass fiber bundles or glass strands) formed by bundling a specified number of glass filaments and cut into a specified length. The number of glass filaments constituting the above-mentioned glass fibers (the number of bundled strands) is preferably 1 to 20,000, more preferably 50 to 10,000, and further preferably 1,000 to 8,000. In addition, the above-mentioned glass fibers are preferably cut into a length in the range of 1.0 to 100.0 mm, more preferably cut into a length in the range of 1.2 to 51.0 mm, further preferably cut into a length in the range of 1.5 to 30.0 mm, particularly preferably cut into a length in the range of 2.0 to 15.0 mm, and most preferably cut into a length in the range of 2.3 to 7.8 mm.
[0083] The roving refers to a state in which glass fibers composed of 10 to 30,000 glass filaments bundled together are not cut.
[0084] The cut fibers are obtained by pulverizing glass fibers consisting of 1 to 20,000 glass filaments bundled together into a length ranging from 0.001 to 0.900 mm by a known method such as a ball mill or a Henschel mixer.
[0085] The resin forming the glass fiber reinforced resin molded product of the present embodiment may be a thermoplastic resin or a thermosetting resin, but from the viewpoint of the recyclability of the resin itself, a thermoplastic resin is preferably used.
[0086] Examples of the thermoplastic resin that forms the glass fiber reinforced resin molded article of the present embodiment include polyethylene, polypropylene, polystyrene, styrene / maleic anhydride resin, styrene / maleimide resin, polyacrylonitrile, acrylonitrile / styrene (AS) resin, acrylonitrile / butadiene / styrene (ABS) resin, chlorinated polyethylene / acrylonitrile / styrene (ACS) resin, acrylonitrile / ethylene / styrene (AES) resin, acrylonitrile / styrene / methyl acrylate (ASA) resin, styrene / acrylonitrile (SAN) resin, methacrylic resin, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyamide, polyacetal, polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and polybutylene terephthalate (PBT). ), polytrimethylene terephthalate (PTT), polycarbonate, polyarylene sulfide, polyethersulfone (PES), polyphenylene sulfone (PPSU), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyarylene ketone, liquid crystal polymer (LCP), fluororesin, polyetherimide (PEI), polyarylate (PAR), polysulfone (PSF), polyamideimide (PAI), polyaminobismaleimide (PABM), thermoplastic polyimide (TPI), polyethylene naphthalate (PEN), ethylene / vinyl acetate (EVA) resin, ionomer (IO) resin, polybutadiene, styrene / butadiene resin, polybutene, polymethylpentene, olefin / vinyl alcohol resin, cyclic olefin resin, cellulose resin, polylactic acid, etc.
[0087] Examples of the polyethylene include high-density polyethylene (HDPE), medium-density polyethylene, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene.
[0088] Examples of the polypropylene include isotactic polypropylene, atactic polypropylene, meta-polypropylene, and mixtures thereof.
[0089] Examples of the polystyrene include general-purpose polystyrene (GPPS) which is atactic polystyrene having an atactic structure, high impact polystyrene (HIPS) obtained by adding a rubber component to GPPS, and syndiotactic polystyrene having a syndiotactic structure.
[0090] Examples of the methacrylic resin include polymers obtained by polymerizing one methacrylic resin selected from acrylic acid, methacrylic acid, styrene, methyl acrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, and fatty acid vinyl esters alone, and polymers obtained by copolymerizing two or more of the methacrylic resins.
[0091] Examples of the polyvinyl chloride include homopolymers of vinyl chloride polymerized by conventionally known methods such as emulsion polymerization, suspension polymerization, microsuspension polymerization, and bulk polymerization, copolymers with monomers copolymerizable with vinyl chloride monomers, and graft copolymers in which vinyl chloride monomers are graft-polymerized onto polymers.
[0092] Examples of the polyamide include polycaprolactam (polyamide 6), polyhexamethylene adipamide (polyamide 66), polybutylene adipamide (polyamide 46), polyhexamethylene sebacamide (polyamide 410), polypentamethylene adipamide (polyamide 56), polypentamethylene sebacamide (polyamide 510), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecanamide (polyamide 612), polydecamethylene adipamide (polyamide 106), polypentamethylene sebacamide (polyamide 56), polypentamethylene sebacamide (polyamide 510), polyhexamethylene dodecanamide (polyamide 610), polyhexamethylene dodecanamide (polyamide 612), polydecamethylene adipamide (polyamide 106), polydecamethylene sebacamide (polyamide 610), polydecamethylene dodecan ... amine (polyamide 1010), polydodecane diamide (polyamide 1012), polyundecanamide (polyamide 11), polyhexamethylene adipamide (polyamide 116), polydodecane amide (polyamide 12), polyxylene adipamide (polyamide XD6), polydecane diamine (polyamide XD10), polymexylene adipamide (polyamide MXD6), polyparaxylene adipamide (polyamide PXD6), polyterephthalamide (polyamide 4T), polypentaphthalamide Methylene terephthalamide (polyamide 5T), polyhexamethylene terephthalamide (polyamide 6T), polyhexamethylene isophthalamide (polyamide 6I), polynonamethylene terephthalamide (polyamide 9T), polydecane terephthalamide (polyamide 10T), polyundemethylene terephthalamide (polyamide 11T), polydodecamethylene terephthalamide (polyamide 12T), polytetramethylene polyphthalamide (polyamide 4I), polybis(3-methyl-4- The invention also includes a copolymer of one component selected from the group consisting of polyamides such as poly(3-methyl-4-aminohexyl)methane terephthalamide (polyamide PACMT), polybis(3-methyl-4-aminohexyl)methane isophthalamide (polyamide PACMI), polybis(3-methyl-4-aminohexyl)methane dodecanamide (polyamide PACM12), and polybis(3-methyl-4-aminohexyl)methane tetradecane diamide (polyamide PACM14), or a mixture thereof.
[0093] Examples of the polyacetal include a homopolymer having an oxymethylene unit as a main repeating unit and a copolymer mainly composed of an oxymethylene unit and containing an oxyalkylene unit having 2 to 8 adjacent carbon atoms in the main chain.
[0094] Examples of the polyethylene terephthalate include polymers obtained by polycondensing ethylene glycol and terephthalic acid or a derivative thereof.
[0095] Examples of the polybutylene terephthalate include polymers obtained by polycondensing 1,4-butanediol and terephthalic acid or a derivative thereof.
[0096] Examples of the polytrimethylene terephthalate include polymers obtained by polycondensing 1,3-propylene glycol and terephthalic acid or a derivative thereof.
[0097] Examples of the polycarbonate include polymers obtained by an ester exchange method in which a dihydroxydiaryl compound and a carbonate such as diphenyl carbonate are reacted in a molten state, and polymers obtained by a phosgene method in which a dihydroxydiaryl compound and phosgene are reacted.
[0098] Examples of the polyarylene sulfide include linear polyphenylene sulfide, cross-linked polyphenylene sulfide that has a high molecular weight by a curing reaction after polymerization, polyphenylene sulfide sulfone, polyphenylene sulfide ether, and polyphenylene sulfide ketone.
[0099] Examples of the modified polyphenylene ether include polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polystyrene, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene copolymer, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / maleic anhydride copolymer, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polyamide, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene / acrylonitrile copolymer, and the like.
[0100] Examples of the polyaryl ketone include polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), and polyetheretherketoneketone (PEEKK).
[0101] As the above-mentioned liquid crystal polymer (LCP), there can be mentioned (co)polymers composed of structural units of one or more components selected from the following components, and the components are: aromatic hydroxycarbonyl units, aromatic dihydroxy units, aromatic dicarbonyl units, aliphatic dihydroxy units, aliphatic dicarbonyl units, etc. as thermotropic liquid crystal polyesters.
[0102] Examples of the fluororesin include polytetrafluoroethylene (PTFE), perfluoroalkoxy resin (PFA), fluorinated ethylene propylene resin (FEP), fluorinated ethylene tetrafluoroethylene resin (ETFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and ethylene / chlorotrifluoroethylene resin (ECTFE).
[0103] Examples of the ionomer (IO) resin include copolymers of olefins or styrene and unsaturated carboxylic acids, in which a part of the carboxyl groups is neutralized with metal ions.
[0104] Examples of the olefin / vinyl alcohol resin include ethylene / vinyl alcohol copolymers, propylene / vinyl alcohol copolymers, ethylene / vinyl acetate copolymer saponified products, and propylene / vinyl acetate copolymer saponified products.
[0105] Examples of the cyclic olefin resin include monocyclic compounds such as cyclohexene, polycyclic compounds such as tetracyclopentadiene, and polymers of cyclic olefin monomers.
[0106] Examples of the polylactic acid include poly-L-lactic acid which is an L-form homopolymer, poly-D-lactic acid which is a D-form homopolymer, and stereocomplex polylactic acid which is a mixture thereof.
[0107] Examples of the cellulose resin include methyl cellulose, ethyl cellulose, hydroxy cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, cellulose acetate, cellulose propionate, and cellulose butyrate.
[0108] In addition, the above-mentioned thermosetting resin for forming the glass fiber reinforced resin molded product of the present embodiment includes: unsaturated polyester resin, vinyl ester resin, epoxy (EP) resin, melamine (MF) resin, phenolic resin (PF), polyurethane resin (PU), polyisocyanate, polyisocyanurate, polyimide (PI), urea (UF) resin, silicone (SI) resin, furan (FR) resin, benzoguanamine (BR) resin, alkyd resin, xylene resin, bismaleimide triazine (BT) resin, diallyl phthalate resin (PDAP) and the like.
[0109] The glass fiber reinforced resin molded product of the present embodiment can be produced, for example, by kneading the chopped strands and the resin in a twin-screw kneader to produce resin pellets, and performing injection molding using the resin pellets to obtain the glass fiber reinforced resin molded product.
[0110] In addition, the above-mentioned glass fiber reinforced resin molded products can be obtained by the following well-known molding methods: injection compression molding, two-color molding, hollow molding, foaming molding (also including supercritical fluid foaming molding), insert molding, in-mold coating molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, compression molding, blow molding, stamping molding, melting method, hand lay-up molding, spraying, resin transfer molding, sheet molding compound molding, integral film pressing molding, pultrusion molding, filament winding, etc.
[0111] In the glass fiber reinforced resin molded product of the present embodiment, the number average fiber length of the glass fiber of the present embodiment is, for example, in the range of 50 to 400 μm, preferably in the range of 75 to 300 μm, more preferably in the range of 100 to 380 μm, further preferably in the range of 120 to 350 μm, particularly preferably in the range of 150 to 320 μm, extremely preferably in the range of 170 to 290 μm, and most preferably in the range of 205 to 285 μm.
[0112] In the glass fiber reinforced resin molded product of the present embodiment, the number average fiber length of the glass fiber of the present embodiment can be calculated by the following method. First, the glass fiber reinforced resin molded product is heated in a muffle furnace at 650°C for 0.5 to 24 hours to decompose organic matter. Then, the remaining glass fiber is moved to a glass dish, and acetone is used to disperse the glass fiber on the surface of the glass dish. Next, the fiber length of more than 1000 glass fibers dispersed on the surface of the glass dish is measured using a stereo microscope, and the average is taken to calculate the number average fiber length of the glass fiber.
[0113] For the purpose of improving the adhesion between glass fiber and resin, improving the uniform dispersibility of glass fiber in the mixture of glass fiber and resin, the surface of the above-mentioned glass fiber contained in the glass fiber reinforced resin molded product of the present embodiment can also be coated with an organic substance. As such an organic substance, a resin or a silane coupling agent can be cited. In addition, the above-mentioned organic substance can also be an organic substance that further contains a composition such as a lubricant or a surfactant in addition to a resin or a silane coupling agent.
[0114] The organic substance covers the glass fiber at a ratio of 0.1 to 2.0 mass % based on the mass of the glass fiber in a state not covered with the organic substance.
[0115] It should be noted that the coating of glass fiber with organic matter can be carried out, for example, by the following method: in the manufacturing process of glass fiber, the above-mentioned sizing agent or adhesive containing the above-mentioned resin, the above-mentioned silane coupling agent or the solution of the composition is applied to the glass fiber using a known method such as a roller coater, and then the glass fiber coated with the above-mentioned resin, the above-mentioned silane coupling agent or the solution of the composition is dried. As the above-mentioned resin, polyurethane resin, epoxy resin, vinyl acetate resin, acrylic resin, modified polypropylene, especially carboxylic acid-modified polypropylene, (poly)carboxylic acid, especially copolymers of maleic acid and unsaturated monomers, etc. can be cited.
[0116] Examples of the silane coupling agent include aminosilane, chlorosilane, epoxysilane, mercaptosilane, vinylsilane, acrylic silane, and cationic silane. The silane coupling agents may be used alone or in combination of two or more.
[0117] Examples of the aminosilane include γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-N′-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-anilinopropyltrimethoxysilane.
[0118] Examples of the chlorosilane include γ-chloropropyltrimethoxysilane and the like.
[0119] Examples of the epoxysilane include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0120] Examples of the mercaptosilane include γ-mercaptotrimethoxysilane and the like.
[0121] Examples of the vinyl silane include vinyltrimethoxysilane and N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane.
[0122] Examples of the acrylic silane include γ-methacryloxypropyltrimethoxysilane and the like.
[0123] Examples of the cationic silane include N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride and N-phenyl-3-aminopropyltrimethoxysilane hydrochloride.
[0124] Examples of the lubricant include modified silicone oil, animal oil and hydrogenated additives thereof, vegetable oil and hydrogenated additives thereof, animal wax, vegetable wax, mineral wax, condensates of higher saturated fatty acids and higher saturated alcohols, polyethylene imine, polyalkyl polyamine alkyl linolenic acid derivatives, fatty acid amides, and quaternary ammonium salts. The lubricants may be used alone or in combination of two or more.
[0125] Examples of animal oils include beef tallow and the like.
[0126] Examples of the vegetable oil include soybean oil, coconut oil, rapeseed oil, palm oil and castor oil.
[0127] Examples of the animal wax include beeswax and lanolin.
[0128] Examples of the vegetable wax include candelilla wax and carnauba wax.
[0129] Examples of the mineral wax include paraffin wax and montan wax.
[0130] Examples of the condensate of a higher saturated fatty acid and a higher saturated alcohol include stearic acid esters such as lauryl stearate.
[0131] Examples of the fatty acid amide include dehydration condensates of polyethylene polyamines such as diethylenetriamine, triethylenetetramine, and tetraethylenepentamine, and fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid.
[0132] Examples of the fourth-stage ammonium salt include alkyltrimethylammonium salts such as lauryltrimethylammonium chloride.
[0133] Examples of the surfactant include nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants. These surfactants may be used alone or in combination of two or more.
[0134] Examples of the nonionic surfactant include ethylene oxide propylene oxide alkyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene-polyoxypropylene-block copolymers, alkyl polyoxyethylene-polyoxypropylene-block copolymer ethers, polyoxyethylene fatty acid esters, polyoxyethylene fatty acid monoesters, polyoxyethylene fatty acid diesters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid ester ethylene oxide adducts, polyoxyethylene stearyl ethers, hydrogenated castor oil ethylene oxide adducts, alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, glycerol fatty acid esters, polyglycerol fatty acid esters, pentaerythritol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyol alkyl ethers, fatty acid alkanolamides, acetylene glycols, acetylene alcohols, ethylene oxide adducts of acetylene glycols, and ethylene oxide adducts of acetylene alcohols.
[0135] Examples of the cationic surfactant include alkyldimethylbenzylammonium chloride, alkyltrimethylammonium chloride, alkyldimethylethylammonium ethylsulfate, higher alkylamine acetates, higher alkylamine hydrochlorides, ethylene oxide adducts of higher alkylamines, condensates of higher fatty acids and polyalkylene polyamines, ester salts of higher fatty acids and alkanolamines, salts of higher fatty acid amides, imidazoline-type cationic surfactants, alkylpyridinium salts, and the like.
[0136] Examples of the anionic surfactant include higher alcohol sulfates, higher alkyl ether sulfates, α-olefin sulfates, alkylbenzene sulfonates, α-olefin sulfonates, reaction products of fatty acid halides and N-methyltaurine, dialkyl sulfosuccinates, higher alcohol phosphates, and phosphates of higher alcohol ethylene oxide adducts.
[0137] Examples of the amphoteric surfactant include amino acid-type amphoteric surfactants such as alkylaminopropionic acid alkali metal salts, betaine-type amphoteric surfactants such as alkyldimethylbetaine, and imidazoline-type amphoteric surfactants.
[0138] The above-mentioned glass fiber reinforced resin molded products can be used, for example, for parts such as housings and frames of portable electronic devices represented by smartphones, automotive electrical components such as battery tray covers or sensors and coil bobbins, electronic equipment components other than portable electronic devices, and electrical connection terminal components.
[0139] Next, examples of the present invention and comparative examples are shown.
[0140] Example
[0141] First, glass raw materials are mixed in such a manner that the glass compositions after melting and solidification will become the compositions of Examples 1 to 20 and Comparative Examples 1 to 4 shown in Tables 1 to 3, thereby obtaining a glass batch. The obtained glass batch is placed in a platinum crucible, and the platinum crucible is kept in an electric furnace at a temperature range of 1400 to 1550°C for 4 hours, and the glass raw materials are melted while being stirred, thereby obtaining a homogeneous molten glass. Next, the platinum crucible containing the molten glass is taken out of the electric furnace, and the molten glass is cooled. Next, after the molten glass is tapped out of the platinum crucible, it is heated at a strain removal temperature (600 to 700°C) for 2 hours to remove the strain of the glass, and it takes 8 hours to cool it to room temperature (20 to 25°C) to obtain block-shaped cullet.
[0142] Next, the elastic modulus, thermal expansion coefficient, fiber diameter variation of glass fibers having a circular cross section, and shape ratio variation of glass fibers having a flat cross section of the glass composition for glass fibers were evaluated in the following manner.
[0143] 〔Elastic modulus〕
[0144] The block-shaped cullet is processed into a test piece of 25 mm×25 mm×5 mm using a cutting machine such as a diamond cutter and a grinder, and the Young's modulus is measured as an index of elastic modulus by an ultrasonic pulse method in accordance with JIS R 1602:1995.
[0145] 〔Coefficient of thermal expansion〕
[0146] The block-shaped cullet is processed into a test piece of 4 mm×4 mm×20 mm using a cutting machine, such as a diamond tool and a grinder. The test piece is heated at a heating rate of 10°C / min, and the elongation is measured at a temperature in the range of 50 to 200°C using a thermomechanical analyzer (manufactured by Hitachi High-Technologies Corporation). The linear expansion coefficient is calculated based on the elongation, thereby measuring the thermal expansion coefficient of the glass fiber.
[0147] [Unevenness of fiber diameter of glass fiber having a circular cross section]
[0148] A glass composition for glass fiber prepared to have a specified composition as a glass raw material is melted in a melting furnace, and the melted composition is spun using a sleeve with a nozzle having more than 200 holes to obtain a glass fiber (filament) with a circular cross section. 50 fibers are randomly selected from the above glass filaments, and the fiber diameter of each filament is measured. The larger percentage X among the following percentages in the above measurement is calculated: the percentage W of the standard deviation of the fiber diameter divided by the average value of the fiber diameter; the percentage of the difference between the maximum value and the average value of the fiber diameter divided by the average value; the percentage of the difference between the minimum value and the average value of the fiber diameter divided by the average value. The case where the percentage W is less than 7.5% and the percentage X is less than 20.0% is evaluated as A; the case where the percentage W exceeds 7.5% and is less than 15.0% and the percentage X is less than 20.0% is evaluated as B, and the case where the percentage W exceeds 15.0% or the percentage X exceeds 20.0% is evaluated as C.
[0149] [Unevenness of the profile ratio of glass fibers having a flat cross section]
[0150] A glass composition for glass fiber having a specified composition is melted in a melting furnace as a glass raw material, and the melted composition is spun using a sleeve with a nozzle having more than 200 holes to obtain a glass fiber (filament) having a flat cross section. 50 fibers are randomly selected from the above glass filaments, and the short diameter, long diameter and converted fiber diameter of each filament are measured. The standard deviation of the ratio of the long diameter to the short diameter (profile ratio) at this time divided by the average value is calculated as a percentage Y, and the standard deviation of the circular converted fiber diameter is divided by the average value as a percentage Z. The case where the calculated percentage Y value is less than 20.0% and the calculated percentage Z value is less than 7.5% is evaluated as A; the case where the calculated percentage Y value exceeds 20.0% or the calculated percentage Z value exceeds 7.5% and the calculated percentage Y value is less than 30.0% and the calculated percentage Z value is less than 15.0% is evaluated as B; the case where the calculated percentage Y value exceeds 30.0% or the calculated percentage Z value exceeds 15.0% is evaluated as C.
[0151] [Table 1]
[0152] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 <![CDATA[siO2 (% by mass)]]> 53.93 53.80 53.96 53.57 54.07 54.04 54.04 53.97 <![CDATA[B2O3 (mass%)]]> 6.23 6.21 6.23 6.19 6.24 6.24 6.24 6.25 <![CDATA[Al2O3 (mass%)]]> 14.15 14.12 14.16 14.06 14.19 14.18 14.18 14.16 CaO (mass%) 22.55 22.49 22.56 22.39 22.60 22.59 22.59 22.56 MgO (mass%) 0.99 0.99 0.99 0.99 1.00 1.00 1.00 0.99 <![CDATA[Na2O (mass%)]]> 0.50 0.50 0.50 0.49 0.50 0.50 0.50 0.50 <![CDATA[K2O (mass%)]]> 0.07 0.07 0.07 0.07 0.07 0.07 0.07 0.07 <![CDATA[Li2O (mass%)]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Na2O + K2O + Li2O (mass%)]]> 0.57 0.57 0.57 0.56 0.57 0.57 0.57 0.57 <![CDATA[TiO2 (mass%)]]> 0.35 0.35 0.35 0.50 0.35 0.35 0.35 0.35 <![CDATA[Fe2O3 (mass%)]]> 0.20 0.20 0.20 0.20 0.20 0.20 0.20 0.20 <![CDATA[F2 (mass%)]]> 0.70 0.69 0.70 0.69 0.70 0.70 0.70 0.70 <![CDATA[SO3 (% by mass)]]> 0.03 0.08 0.03 0.10 0.03 0.03 0.03 0.05 <![CDATA[Cr2O3 (mass%)]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 ZnO (mass%) 0.05 0.25 0.00 0.50 0.00 0.05 0.00 0.10 <![CDATA[P2O5 (mass%)]]> 0.25 0.25 0.25 0.25 0.05 0.05 0.10 0.10 <![CDATA[ZnO + SO3 (mass%)]]> 0.08 0.33 0.03 0.60 0.03 0.08 0.03 0.15 BaO+SrO (mass %) 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 Total (mass %) 100.00 100.00 100.00 100.00 100.00 100.00 100.00 100.00 <![CDATA[(SI / C) 2 ×(A / T)×{P / (SO+z)} 1 / 4 ]]> 307.4 215.4 393.2 129.3 263.7 206.1 313.3 209.2 Elastic modulus(GPa) 88.0 88.0 88.0 88.0 88.0 88.0 88.0 88.0 Thermal expansion coefficient (ppm / ℃) 5.6 5.6 5.6 5.7 5.6 5.6 5.6 5.6 Uneven fiber diameter A A A A A A A A Uneven shape ratio A A A A A A A A
[0153] [Table 2]
[0154] Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Embodiment 15 Example 16 <![CDATA[SiO2 (mass%)]]> 54.00 53.86 53.88 53.82 53.55 52.97 53.28 52.10 <![CDATA[B2O3 (mass%)]]> 6.24 6.22 6.23 6.23 6.19 6.12 6.16 6.03 <![CDATA[Al2O3 (mass%)]]> 14.17 14.14 14.14 14.12 14.05 13.90 13.98 13.67 CaO (mass%) 22.58 22.52 22.52 22.50 22.39 22.14 22.27 21.78 MgO (mass%) 0.99 0.99 0.99 0.99 0.99 0.98 0.98 0.96 <![CDATA[Na2O (mass%)]]> 0.50 0.50 0.50 0.50 0.49 0.49 0.49 0.48 <![CDATA[K2O (mass%)]]> 0.07 0.07 0.07 0.07 0.07 0.07 0.07 0.07 <![CDATA[Li2O (mass%)]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Na2O + K2O + Li2O (mass%)]]> 0.57 0.57 0.57 0.57 0.56 0.56 0.56 0.55 <![CDATA[TiO2 (mass%)]]> 0.35 0.35 0.50 0.35 0.35 1.00 0.35 1.50 <![CDATA[Fe2O3 (mass%)]]> 0.20 0.20 0.20 0.20 0.20 0.20 0.20 0.19 <![CDATA[F2 (% by mass)]]> 0.70 0.69 0.69 0.69 0.69 0.68 0.69 0.67 <![CDATA[SO3 (mass%)]]> 0.05 0.08 0.03 0.03 0.03 0.20 0.03 0.30 <![CDATA[Cr2O3 (mass%)]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 ZnO (mass%) 0.10 0.25 0.00 0.00 0.00 1.00 0.00 1.50 <![CDATA[P2O5 (mass%)]]> 0.05 0.13 0.25 0.50 1.00 0.25 1.50 0.75 <![CDATA[ZnO + SO3 (mass%)]]> 0.15 0.33 0.03 0.03 0.03 1.20 0.03 1.80 BaO+SrO (mass %) 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 Total (mass %) 100.00 100.00 100.00 100.00 100.00 100.00 100.00 100.00 <![CDATA[(sI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ]]> 175.9 183.1 275.0 466.4 551.7 53.8 608.0 41.9 Elastic modulus(GPa) 88.0 88.0 88.4 88.0 88.0 89.5 88.0 90.3 Thermal expansion coefficient (ppm / ℃) 5.6 5.6 5.6 5.5 5.5 5.8 5.6 5.9 Uneven fiber diameter A A A A A A A A Uneven shape ratio A A A A A A B B
[0155] [Table 3]
[0156] Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[SiO2 (mass%)]]> 52.29 53.01 52.74 51.37 52.19 51.50 45.80 49.00 <![CDATA[B2O3 (mass%)]]> 6.06 6.12 6.09 5.94 6.04 6.1 5.3 6.1 <![CDATA[Al2O3 (mass%)]]> 13.72 13.91 13.84 13.48 13.70 13.60 12.02 12.80 CaO (mass%) 21.86 22.16 22.05 21.47 21.82 22.40 19.15 20.50 MgO (mass%) 0.96 0.98 0.97 0.95 0.96 1.00 0.84 1.00 <![CDATA[Na2O (mass%)]]> 0.48 0.49 0.49 0.47 0.48 0.44 0.42 0.42 <![CDATA[K2O (mass%)]]> 0.07 0.07 0.07 0.07 0.07 0.06 0.06 0.06 <![CDATA[Li2O (mass%)]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 <![CDATA[Na2O + K2O + Li2O (mass%)]]> 0.55 0.56 0.56 0.54 0.55 0.50 0.48 0.48 <![CDATA[TiO2 (mass%)]]> 1.50 0.35 0.35 2.00 0.35 0.32 7.50 4.20 <![CDATA[Fe2O3 (mass%)]]> 0.19 0.20 0.19 0.19 0.19 0.17 0.17 0.18 <![CDATA[F2 (mass%)]]> 0.67 0.68 0.68 0.66 0.67 0.67 0.59 0.59 <![CDATA[SO3 (mass%)]]> 0.30 0.03 0.03 0.40 0.03 0.02 0.50 0.50 <![CDATA[Cr2O3 (mass%)]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 ZnO (mass%) 1.50 0.00 0.00 2.00 0.00 0.02 7.50 4.20 <![CDATA[P2O5 (mass%)]]> 0.40 2.00 2.50 1.00 3.50 3.70 0.15 0.45 <![CDATA[znO + SO3 (mass%)]]> 1.80 0.03 0.03 2.40 0.03 0.04 8.00 4.70 BaO+SrO (mass %) 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 Total (mass %) 100.00 100.00 100.00 100.00 100.00 100.00 100.00 100.00 <![CDATA[(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ]]> 35.9 649.8 683.5 31.0 736.0 696.7 3.4 9.7 Elastic modulus(GPa) 90.3 88.0 88.0 91.0 88.2 88.2 99.3 94.3 Thermal expansion coefficient (ppm / ℃) 5.9 5.6 5.6 6.0 5.7 5.7 7.1 6.4 Uneven fiber diameter A A B B C C C C Uneven shape ratio B B C C C C C C
[0157] It is obvious from Tables 1 to 3 that the glass compositions for glass fibers of Examples 1 to 20, in which the content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO, and the content SO of SO3 satisfy the formula (1), can suppress the unevenness of the fiber diameter of the glass fibers obtained using the glass compositions for glass fibers. On the other hand, it is obvious that the glass compositions for glass fibers of Comparative Examples 1 to 4, in which the content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO, and the content SO of SO3 do not satisfy the formula (1), can suppress the unevenness of the fiber diameter of the glass fibers obtained using the glass compositions for glass fibers.
Claims
1. A glass composition for glass fiber, characterized in that: Relative to the total amount of the glass composition for glass fiber, it comprises: 45.60-55.90 mass % SiO2, 10.00~16.00 mass% of Al2O3, 4.10 to 8.00 mass % of B2O3, 17.00-25.00 mass% CaO, 0.01 to 9.50 mass% TiO2, 0.03~7.00 mass% of P2O5, 0.00 to 9.50 mass% of ZnO, 0.00~2.00 mass% SO3, Total amount of ZnO and SO3 in the range of 0.01 to 11.50 mass %, Na2O, K2O and Li2O in the range of 0.00 to 2.0 mass % in total, The content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO and the content SO of SO3 satisfy the following formula (1): 15.0≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤690.1…(1).
2. The glass composition for glass fiber according to claim 1, characterized in that: The content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO and the content SO of SO3 satisfy the following formula (2): 33.5≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤666.7…(2).
3. The glass composition for glass fiber according to claim 1, characterized in that: The content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO and the content SO of SO3 satisfy the following formula (3): 47.8≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤579.8…(3).
4. The glass composition for glass fiber according to claim 1, characterized in that: The content SI of SiO2, the content A of Al2O3, the content C of CaO, the content T of TiO2, the content P of P2O5, the content Z of ZnO and the content SO of SO3 satisfy the following formula (4): 91.5≤(SI / C) 2 ×(A / T)×{P / (SO+Z)} 1 / 4 ≤552.0…(4).
5. A glass fiber, characterized in that: The glass fiber is formed from the glass composition for glass fibers according to any one of claims 1 to 4.
6. A glass fiber reinforced resin molded product, characterized in that: The glass fiber according to claim 5 is included.
Citation Information
Patent Citations
Apparatus for treating frp waste
JP1994234879A
Glass fiber composition
CN102849957A